Rozległe zmiany chorobowe w obrębie szkieletu ze średniowiecznego (XIV — XV w.) Szczecina - Gładykowska-Rzeczycka, Judyta Julia (Polskie Towarzystwo Antropologiczne, 1988)
EXTENSIVE DISEASE CHANGES OF THE SKELETON FROM MEDIAEVAL SZCZECIN. The changes provide an interesting example of Hyperostosis frontalis interna referred to by pathologists as the Morgagni-Stewart-Morel syndrome.
EXTENSIVE DISEASE CHANGES OF THE SKELETON FROM MEDIAEVAL SZCZECIN